Bilateral Punctal Stenosis Following Netarsudil Therapy in Fuchs Endothelial Dystrophy: A Case Report - Rohan Jagadish; Nilesh Balaji Giri; Gautami Ramesh Laturkar; Kritika Aggarwal; Saujas Shah (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Netarsudil, a Rho-Associated Protein Kinase (ROCK) inhibitor, is being increasingly used in the management of glaucoma and corneal endothelial disorders. Although conjunctival hyperaemia and corneal verticillata are well-recognised adverse effects, lacrimal drainage abnormalities have rarely been reported. The authors described a 52-year-old male with Fuchs endothelial dystrophy who developed progressive bilateral epiphora and punctal stenosis following initiation of topical Netarsudil 0.02% eye drops. The patient developed worsening watering and redness approximately four months after initiation of therapy. Slit-lamp examination revealed bilateral conjunctival congestion, corneal guttae with stromal oedema and cicatricial narrowing of both upper and lower puncta. Specular microscopy demonstrated reduced endothelial cell density bilaterally, while anterior segment optical coherence tomography showed increased central corneal thickness. Other causes of acquired punctal stenosis including trauma, autoimmune disease, cicatrising conjunctivitis, Stevens-Johnson syndrome and alternative medication-induced aetiologies were excluded clinically. Despite discontinuation of Netarsudil and initiation of preservative-free lubricants, punctal fibrosis persisted, necessitating bilateral punctoplasty with symptomatic improvement on follow-up. The temporal relationship with drug initiation, exclusion of alternate aetiologies and stabilisation after discontinuation supported a probable adverse drug reaction according to World Health Organisation – Uppsala Monitoring Centre (WHO-UMC) causality assessment criteria. The present case highlights a rare but clinically significant adverse effect associated with Netarsudil therapy and emphasises the importance of early recognition and punctal evaluation in patients receiving prolonged ROCK inhibitor therapy.